Pengembangan Modul Pembelajaran Matematika Berbasis Problem Based Learning Siswa SMP Negeri 3 Bawolato - Bawamenewi, Eniman; Lase, Sadiana; Telaumbanua, Yakin Niat; Mendrofa, Netti Kariani (Imajiner: Jurnal Matematika dan Pendidikan Matematika, 2025)
This research was motivated by findings in the problem limitation, namely that students' mathematics learning outcomes had not yet reached the Minimum Mastery Criteria (KKM). Many students considered mathematics to be difficult and boring, and the lack of instructional materials contributed to the ineffectiveness of the learning process. To overcome this issue, a mathematics learning module based on the Problem Based Learning (PBL) model was developed to enhance students' active involvement. This study aims to develop a module that is valid, practical, and effective for use in junior high school mathematics instruction. The research adopted the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The instruments used in this study included validation questionnaires, practicality questionnaires, effectiveness questionnaires, and learning outcome tests. The subjects of the research were one mathematics teacher and eighteen Grade VIII students at SMP Negeri 3 Bawolato. The data collected consisted of both quantitative and qualitative data. The validation results indicated that the module was highly valid, with a score of 91.6% from the content expert, 88.8% from the language expert, and 87.5% from the design expert. The module was considered highly practical based on the teacher's response (92.5%) and students' response (89.8%). The module's effectiveness was demonstrated by an increase in students’ learning outcomes, from an average score of 25.67 (low category) to 84.55 (very good category). Thus, the mathematics module based on the Problem-Based Learning model meets the criteria of validity, practicality, and effectiveness, and is suitable for use in mathematics learning at the junior high school level.